Memoria E Culture: Una Questione Di Presente = MEMORY AND CULTURES : A MATTER OF THE PRESENT. - Pandolfi, Luca (Rivista di scienze dell'educazione, 2021)
The article aims to introduce the three subsequent contributions whose focus is the educational function of memory in three different cultural contexts. Making "memory" is a complex issue and requires a conscious gaze of the ambiguity and plurality of this operation. It is necessary to be attentive to the "present" of the narrator and to the complexity of the intertwining of memory, identity representation and cultural identification and / or belonging. The brief introduction underlines the task of thinking about the past in order to build the future, while remembering how much a question of the present is. (English)